Online patriarchal bargains and social support: Struggles and strategies of unwed single mothers in China - ZHAO, Xiaoman (Institutional Knowledge at Singapore Management University, 2021)
Patriarchal bargains have been studied in many settings as a strategy that helps women circumvent constraints and forge spaces for individual empowerment. Despite the growing use of mediated communication, little is known about how patriarchal bargains are enacted and realized within online interactions such as in discussion forums. By analyzing how Chinese unwed single mothers renegotiate the state’s oppressive population control and gender policies through their online activity, this study proposes the concept of “online patriarchal bargain” to extend patriarchal bargain theory to women’s Internet use. It further explores linkages between social support and patriarchal bargain to elucidate how support is integral to enacting agency in the face of forbidding systemic constraints. The findings also delve into the role of therapeutic culture in the day-to-day experiences of women, especially those in marginalized communities.